2010
DOI: 10.1177/0037549710373571
|View full text |Cite
|
Sign up to set email alerts
|

Online railway delay management: Hardness, simulation and computation

Abstract: Delays in a railway network are a common problem that railway companies face in their daily operations. When a train is delayed, it may either be beneficial to let a connecting train wait so that passengers in the delayed train do not miss their connection, or it may be beneficial to let the connecting train depart on time to avoid further delays. These decisions naturally depend on the global structure of the network, on the schedule, on the passenger routes and on the imposed delays. The railway delay manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…In the transportation industry, the time spent for waiting is related to service assessment (Mishalani & McCord, 2010;Vansteenwegen & Oudheusden, 2006). Train delays are often considered by passengers as an indication of poor service (Berger, Hoffmann, Lorenz, & Stiller, 2011). A long delay can negatively affect overall service evaluation and increase the severity of negative affective responses such as anger because of the uncertainty created by such delays (Taylor, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…In the transportation industry, the time spent for waiting is related to service assessment (Mishalani & McCord, 2010;Vansteenwegen & Oudheusden, 2006). Train delays are often considered by passengers as an indication of poor service (Berger, Hoffmann, Lorenz, & Stiller, 2011). A long delay can negatively affect overall service evaluation and increase the severity of negative affective responses such as anger because of the uncertainty created by such delays (Taylor, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…All works in this class derive their solution heuristically. Berger et al (2011b) develop TOPSU-RDM, a simulation platform that evaluates different heuristics for the DM problem, drawing delays from underlying distribution functions. The platform combines the tasks of building a model, finding an appropriate solution algorithm and experimentally evaluating it.…”
Section: Macroscopic Stochastic Models [ ]mentioning
confidence: 99%
“…Li et al (2009) showed that the VRSP is an NP-hard problem. Corman et al (2010) demonstrated that the train conflict detection and resolution (CDR), a sub-class of the TRP, is NP-complete, while Berger et al (2011b) proved that the online railway delay management (ORDM) problem is PSPACE-hard (Arora and Barak 2009). Fig.…”
Section: Basic Models and Problem Formulationsmentioning
confidence: 99%
“…Simulation experiments show that a real-time rescheduling system could significantly reduce the total delays even in the case where additional trains are added to the timetable. Simulation has also been used by Berger et al (2011b) in order to solve the ORDM problem, in which passengers have a fixed network route, but are allowed to adapt the choices of the trains based on delays. The major objective is to minimize the total delay of passengers.…”
Section: Train Rescheduling Modelsmentioning
confidence: 99%